Hodgkin’s Lymphoma Revealed by Hemophagocytic Lymphohistiocytosis in a Child - Sarra Benmiloud; Mohamed Hbibi; Sana Chaouki; Sana Abourazzak; Moustapha Hida (Case Reports in Pediatrics)
Hemophagocytic lymphohistiocytosis (HLH) is a severe life-threatening disorder, responsible for extensive phagocytosis of hematopoietic cells and causing a multisystem organ failure. If lymphomas are common causes of HLH, the association with Hodgkin’s lymphoma is rarely described in children. We report a case of a 9-year-old boy presenting with HLH as an initial manifestation of Hodgkin’s lymphoma. He has been suffering from persistent high fever, asthenia, weight loss, and hepatosplenomegaly with no lymphadenopathy. The diagnosis of HLH secondary to infectious disease was initially worn. The patient received high-dose intravenous immunoglobulin with broad-spectrum antibiotics. However, his state got worse with the onset of dry cough and pleural effusion. Histopathologic examination of pleural fluid showed the presence of Reed-Sternberg cells. The outcome was favorable after treatment by corticosteroid and chemotherapy. Hodgkin’s lymphoma revealed by HLH is a source of delayed diagnosis and should be borne in mind in children.